Efficacy and Safety of Single-Session Radiofrequency Ablation in Treating Benign Thyroid Nodules: A Short-Term Prospective Cohort Study - Van Bang Nguyen; Thi Xuan Nguyen; Van Vy Hau Nguyen; Hai Thuy Nguyen; Dinh Toan Nguyen; Chi Van Le (International Journal of Endocrinology)
Objective. The aims of this study are to evaluate the safety and efficacy of RFA in the treatment of benign thyroid nodule(s) and to find independent factors related to the volume reduction rate of the nodule(s). Materials and Methods. This short-term prospective study from a single medical center was conducted on 93 benign thyroid nodules in 93 patients treated with RFA. Two basic techniques were used: the trans-isthmic approach and moving-shot technique. Clinical and ultrasonography examinations were performed at 1- and 3-month follow-up after the treatment session. Primary outcomes included volume reduction ratio (VRR) at 1-month and 3-month follow-ups; secondary outcomes were therapeutic success rate and complications. Multiple linear regression analysis was used to determine independent factors associated with VRR. Results. A final sample of 78 patients with 78 nodules, given participant rate 83.8% (including 60 solid nodules, 16 predominantly cystic nodules, and 2 thyroid cysts), was followed up for 3 months. The mean volume reduction ratio was 41.47% and 64.72% after 1-month and 3-month follow-ups, respectively. The therapeutic success rate was 30.8% at 1-month and 84.6% at 3-month follow-ups. Symptom score and cosmetic score improved significantly. There was no change in thyroid function tests. Two minor complications (transient voice change) were found. The multiple linear regression analysis showed that the internal component of the nodules significantly related to the VRR during the 3-month follow-up (β = 23.00; 95%CI (7.59–38.45)). Conclusion. RFA was demonstrated as a safe and effective option for benign thyroid nodules treatment. It can be used as an alternative treatment with encouraging results.